PENGARUH PENGGUNAAN VAPOR CARBURETOR METODE BUBBLING DAN VARIASI BAHAN BAKAR TERHADAP EMISI GAS BUANG PADA MOTOR SUPRA X - Dedi Usman; Ranto Ranto; Ngatou Rohman (Fakultas Keguruan dan Ilmu Pendidikan Universitas Sebelas Maret Surakarta, 2019)
The objectives of this study were: (1) To investigate the effect of using the Vapor Carburetor Bubbling method on exhaust emissions produced on the Supra X 100 CC motorcycle in 2003, (2) To investigate the effect of using pertalite and pertamax fuels on exhaust emissions in the motorcycle. Supra X 100 CC motorcycles in 2003, (3) To investigate the use of the Vapor Carburetor with the Bubbling method that uses Pertamax and pertalite fuels to exhaust gas emissions on the 2003 Supra X 100 CC motorcycle. This research is a comparative quantitative research with experimental research type. This study used a 2X2 factorial research design. The sample used was the Supra X 100cc motorcycle engine in 2003 with frame number MH1KEVA153K563997 and engine number KEVAE1561218. Data obtained from exhaust emission testing using a Gas Analyzer installed on the exhaust of a 2003 Supra X 100CC motorcycle with a Conventional Carburetor and a Vapor Carburetor at idle engine speed conditions, namely 800 rpm - 1,400 rpm and variations of pertalite fuel variations (RON 90) and Pertamax (RON 92). The test time is 20 seconds after the probe on the Gas Analyzer is inserted into the exhaust. The data analysis technique used in this research is comparative quantitative descriptive. The exhaust emission test was carried out at the Surakarta Work Training Agency (BLK).The results obtained from this study are: (1) The use of the Vapor Carburetor in the Bubbling method produces lower exhaust emissions compared to the Conventional Carburetor on the Supra X 100cc motorbike in 2003. (2) The type of pertalite fuel produces less exhaust emissions in the motorcycle. appeal to Pertamax. (3) The interaction effect of using the type of carburetor and the type of fuel that produces the lowest exhaust gas emissions is the combination of the use of the Vapor Carburetor with the bubbling and pertalite methods, namely 0.43% CO and 280 ppm HC.